The influence of nitric oxide synthases inhibitor Т1023 on the development of radiation pneumofibrosis in rats - A. S. Saburova; M. V. Filimonova; V. V. Yuzhakov; L. I. Shevchenko; N. D. Yakovleva; L. N. Bandurko; A. E. Koretskaya; N. K. Fomina; V. O. Saburov; A. S. Filimonov (Радиационная гигиена, 2020)
The purpose of the work was to study the ability of the NOS inhibitor T1023 to prevent late radiation injuries. Methods: the effects of T1023 (75 mg / kg, once i.p. 30 minutes before the irradiation) on the development of post-radiation pulmonitis and pneumofibrosis in rats with thoracic exposure to g-radiation at  a dose of 12.5 Gy were studied histopathologically and morphometrically. The results of the studies showed that there wasn’t a significant objective effect of T1023 on the development of early radiation-induced lung injuries  (9 weeks after irradiation). But it prevented late radiation induced lung injuaries (26 weeks after irradiation) – there were a significant lesser pathomorphological manifestations of post-radiation pulmonitis, proliferation of connective tissue and the development of fibrotic changes in the lung parenchyma. At this stage, the action of T1023 clearly contributed to the preservation of the normal histostructure of the lungs, reducing by 40% the content of compaction zones in the parenchyma. The ability of the NOS inhibitor T1023 to significantly limit the development of lungs late radiation reaction confirms the promise of further development  of this compound as a means for prevention radiation therapy complications.